Treatment and follow-up of persistent granulomatous cheilitis with intralesional steroid and metronidazole - Coskun, Basak; Saral, Y.; Cicek, D.; Akpolat, N. (My University, 2004)
Granulomatous cheilitis (GC) is a chronic edema which frequently affects the upper lip due to granulomatous inflammation. Its etiology is currently unknown. This rare disease is generally accompanied by Melkersson-Rosenthal syndrome (MRS), characterized by scrotal tongue, orofacial edema and facial paralysis. However, it is also known to develop only with orofacial edema. Granulomatous cheilitis is a difficult disease to treat because of recurrences. There are contradictory reports about the results of treatment without surgical intervention and the rates of recurrence. Our case was a 57-year-old female patient who was characterized by orofacial edema only. The edema and erythema had persisted for 1 year before admission. In the present case, application of intralesional corticosteroid treatment as a total of three injections over 3 consecutive months (one injection per month) and the accompanying metronidazole treatment brought about successful results. No recurrence was observed in the follow-up.
Keywords: Granulomatous cheilitis; Intralesional corticosteroid; Melkersson-Rosenthal syndrome; Metronidazole